PERBEDAAN PERTUMBUHAN BAYI YANG DIBERIKAN ASI EKSKLUSIF DAN YANG DIBERIKAN SUSU FORMULA DI WILAYAH KERJA PUSKESMAS DUNGINGI KOTA GORONTALO - Harismayanti Harismayanti; Ani Retni; Ainun Nurnaningsih Alade (Universitas Muhammadiyah Gorontalo, 2020)
This research was conducted at Dungingi health centre work area. The objective was to determine the difference of infant’s growth that given exclusive breastfeeding and formula milk at Dungingi health centre. The design used analytic observational with cross sectional approach. The samples in this research are 34 samples. This research used statiscal test of independent T test. The result obtained there is no significance differences between infant’s body weight that given exclusive breastfeeding with formula milk with p value 0,240 (>α 0,05). Theres is no significance differences of infant’s tall that given exclusive breastfeeding with formula milk withp value 0,105 (>α 0,05). Thus Ho is rejected. The conclusion of the research was there is no differences of infat’s growth that given exclusive breastfeeding with formula milk.